Valency Types in South Ethiosemitic Languages: General Articles - Zeleke, Tsige Yohannes; Asfawwesen, Desalaegn Hagos; Mazengia, Shimels (Journal for Semitics, 2023)
This article analyses the main characteristics of verb valency types and the behaviour of verbs in morphosyntactic structures in South Ethiosemitic languages. To achieve the objective, native speaker informants, written texts, and introspection (for Amharic) were used as sources of data. The findings reveal that six valency types of verbs are in use in the languages: avalent, monovalent, bivalent, trivalent, and a valency of ambivalent verbs with one or two arguments, as well as intransitive verbs with a cognate object. Except for the type that concerns avalent verbs, the rest are highly productive. The valency types were differentiated by the required clause elements that precede the verb (e.g., direct object, indirect object, or locative adverbial). Except for the avalent type, all the rest may include obligatory subject(s) and, in some cases, optional adjunct(s).